Impact of Dalteparin Sodium and Luteal Phase Support on Serum Markers, Interleukins, and Pregnancy Outcomes in Patients with In Vitro Fertilization Failure - Lei, Jinmei (Journal of Medical Biochemistry, 2025)
Introduction: In vitro fertilization-embryo transfer (IVF-ET) remains a challenging treatment for infertility, particularly in patients with repeated implantation failures.  Dalteparin sodium (DS), a low molecular weight heparin, has shown promise in improving IVF outcomes due to its antithrombotic and immunomodulatory properties. This study investigated the effects of DS combined with luteal phase support (LPS) on serum markers, interleukins, and pregnancy outcomes in patients with a history of repeated IVF failure.Materials and Methods: This retrospective study included 80 patients with a history of repeated IVF failure who underwent assisted reproduction at our center. Patients were randomly assigned to receive either LPS alone (Ctrl group, n=40) or LPS combined with daily subcutaneous injections of DS (Exp group, n=40).  Serum levels of β-hCG, FSH, E2, LH, CA-125, and interleukin-6 (IL-6) were measured and compared between the groups.Results: The Exp group demonstrated significantly higher clinical pregnancy rates (CPR) and embryo implantation rates (EIR) compared to the Ctrl group (P